The learning experience of postgraduate students:Emergent themes. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
In recent years,postgraduate education in Malaysian public universities has undergone tremendous changes. A variety of trends and factors continue to affect higher education institutions that offer postgraduate programmes to a large number of local and foreign postgraduate students. The transformation of higher education from a selected elite clientele to a wider deserving target is not only restricted to the undergraduate level but also applies to postgraduate education. In Universiti Sains Malaysia, the number of postgraduate student enrolments has increased three folds.